EFEKTIVITAS PEMANFAATAN APLIKASI TARTEEL DALAM MENINGKATKAN KEMAMPUAN HAFALAN AL-QUR’AN PESERTA DIDIK - Rosmiyati, Rosmiyati; Makbuloh, Deden; Hasanah, Uswatun; Diana, Nirva; Jalaluddin, Jalaluddin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Memorizing the Qur'an which is prioritized because of its own will without coercion from others or parents, where the will is driven from the belief in spiritual values with sincere intentions solely for Allah. One way to overcome the laziness of students or memorizers of the Qur'an is to provide motivation, for example, such as both parents memorizing the Qur'an, giving crowns to parents in the afterlife or telling stories of memorizers of the Qur'an. The purpose of this study is to determine the effectiveness of the use of the Tarteel application in improving the memorization ability of the Al-Qur'an of students at MAN 1 Tanggamus. The research method used in this study is quantitative research, with a research design using Pretest-Posttest. Data collection was done with tests, interviews and documentation. The results of this study indicate that there is an effectiveness of utilizing the Tarteel application in improving the ability to memorize the Qur'an of XI social studies class students at MAN 1 Tanggamus. This can be seen by proving the Effect size test with the acquisition of d = 1.467> 0.8 whose category is high. So it is concluded that the use of the Tarteel application in improving the ability to memorize the Qur'an of students. For the effectiveness of the Tarteel application, this can be proven by the average value of N-Gain in Class XI IPS 7 (Experiment class) is greater than Class XI IPS 5 (Control class) with a value of 0.68> 0.47.